Two-stage evolution of magnetic correlations in the spiral spin liquid material Ca10Cr7O28 - Koo, Changhyun; Park, Jaena; Werner, Johannes; Lee, Suheon; Balz, Christian; Islam, A. T. M. Nazmul; Oshima, Yugo; Lake, Bella; Choi, Kwang-Yong; Klingeler, Rüdiger (Physical review, 2025)
We present an X-band and tunable high-frequency/high-field electron spin resonance (HF-ESR) study of single-crystalline Ca10⁢Cr7⁢O28, which constitutes alternating antiferromagnetic and ferromagnetic kagome bilayers. At high temperatures, a phonon-assisted relaxation process is evoked to account for the pronounced increase of the linewidth in an exchange-narrowing regime (𝑘B⁢𝑇≫𝐽). In contrast, at low temperatures (𝑘B⁢𝑇≲𝐽), a power-law behavior in line narrowing is observed. Our data reveal two distinct power-law regimes for the linewidth which crossover at 𝑇*≈7.5K. Notably, the intriguing evolution of the ESR linewidth in this alternating kagome bilayer system with opposite sign of exchange interactions highlights distinct spin dynamics compared to those in a uniform kagome antiferromagnet.
Die Ziffern im Titel sind tiefgestellt
Online veröffentlicht: 19. März 2025
Gesehen am 05.11.2025